Innovations and achievements in modern biotechnology - Lazebnyk, Vladyslav; Mamchur, Olga (My University, 2014)
Modern biotechnology is used to distinguish newer applications of biotechnology, such as genetic engineering and cell fusion from more conventional methods such as breeding, or fermentation; and to describe a range of processes and techniques especially at the molecular level.
Keywords: генна інженерія; генетична модифікація; ген маніпуляції; особливий інтерес; людський інсулін; генная инженерия; генетическая модификация; ген манипуляции; особый интерес; человеческий инсулин; genetic engineering; genetic modification; gene manipulation; particular interest; human insulin; кафедра іноземних мов професійного спрямування